347 Histopathology of Necrotic Spinal Cord Tissue Exudate Collected During Surgical Implantation of a Biodegradable Scaffold Following Acute Spinal Cord Injury: Pre-clinical and Clinical Findings - Lee, K Stuart; Boyer, Philip J; Hsieh, Patrick C; Hurth, Kyle M; Guest, James D; Aimetti, Alex; Layer, Richard T; Moore, Simon W; Ulich, Thomas (Neurosurgery, 2017)
Abstract INTRODUCTION Acute implantation of biodegradable scaffolds following spinal cord injury (SCI) has been shown pre-clinically to reduce chronic cavitation, increase white matter sparing, and increase the deposition of neuropermissive remodeled tissue. The surgical procedure of scaffold implantation allows for the gentle removal of acutely necrotic tissue resulting in a cavity in which the scaffold is placed. Here we report for the first time on the histopathological findings in both animal and human tissue specimens. METHODS Pre-clinically, experimental spinal cord contusion injuries were performed as previously reported in pigs. Clinically, the ongoing INSPIRE study (NCT02138110) is currently enrolling baseline T2-T12/L1 subjects with neurologically complete (AIS A) SCI within 96 hours of injury. The surgical procedure for implantation consists of durotomy and sometimes myelotomy. Commonly, damaged spinal cord tissue under pressure spontaneously extrudes after piotomy in pure contusion injuries. This tissue sample is collected and submitted for histopathologic analysis. RESULTS >24 hours post severe contusion/compression injury in a pig model, hematoxylin and eosin-stained (H&E) paraffin sections revealed myelin and axonal degeneration along with numerous scattered spheroids (swollen axons) with hemorrhage and acute inflammation at the wound site. Surgical pathology reports document neuropil disruption and devitalization in samples collected during surgery at 40 and 82 hours post-injury. In the patient implanted at 40 hours, the tissue specimen contained fragments of disrupted neuropil with swollen and fragmented axons as evaluated by H&E and neurofilament immunohistochemistry. CONCLUSION Severe SCI leads to the rapid formation of irreversibly damaged parenchyma. Our findings in animal and human tissue samples revealed acute tissue disruption and devitalization within 24–82 hours post-injury. This time frame was too short to appreciate phagocytosis, gliosis, or axon sprouts. Future patient enrollment and tissue collection in the ongoing clinical study will continue to build upon these initial observations.